PERSIAPAN PRANIKAH DAN SOSIALISASI KESEHATAN REPRODUKSI PADA CALON PENGANTIN DI KUA KOTA JUANG KABUPATEN BIREUEN - Herrywati Tambunan; Nurhidayati; Siti Rahmah; Cut Syifaul Hayati; Hurum Maksura; Asmaul Husna; Desi Fitriana (LPPM Universitas Al Muslim, 2024)
Maternal and infant morbidity and mortality rates can be prevented by preparing for pregnancy during the pre-pregnancy period. One indicator of the success of development in the health sector is the maternal and infant mortality rate, which represents the quality of maternal health. Pregnancy planning is an important effort to prevent high-risk pregnancies. Reproductive health plays an important role in the prospective bride and groom's ability to conceive offspring, thus preparation need to be well planned. It is by providing guidance and information, as well as pre-marital counseling to prospective brides and grooms, because the quality of marriage is determined by the preparedness and maturity of both prospective marriage partners in facing married life. The aim of carrying out this activity was to increase the knowledge of prospective brides and grooms about reproductive health to prepare for pregnancy. The method used was through counseling in several stages, starting from the preparation stage, implementation and evaluation stage. At the implementation stage, the material is delivered and leaflets were distributed to participants. The community service activities were carried out at KUA Juang City District. Juang City District, Bireuen, Aceh on May 22, 2024. The results of the implementation of this activity showed an increase in the knowledge of the prospective bride and groom, as evidenced by the discussion session, participants were enthusiastic in asking questions and during the evaluation, the prospective bride and groom understood the content of the material that had been presented. Health assistance from the pre-marital period needs to be a priority program to support efforts to increase the pregnancy readiness of prospective mothers.